(untitled) (Brazilian Journal of Health Research, 2025)
Introduction: Colorectal cancer is a common neoplasm in individuals over 50 years old, with rising incidence in younger populations. Objectives: Given its high prevalence, assessing epidemiological pattern changes is essential. Method: This observational, descriptive, cross-sectional study analyzed DataSus epidemiological databases on hospitalized colorectal cancer patients in Brazil. Results: Between 2015 and 2023, 683,388 hospitalizations were recorded (422,100 colon; 261,288 rectosigmoid/anal canal), with 50.7% male, 53% white, 31.54% brown, and 4.2% black. The southeast region had the most cases, and 19.7% were under 50 years old. Espírito Santo, with 1.87% of Brazil’s population, accounted for 3.54% of hospitalizations, predominantly brown (61%) and with a higher female prevalence (50.1%). From 2016 to 2023, colon cancer cases increased by 39%, and rectosigmoid/anal canal cancer by 38%. Hospitalizations among black individuals rose by 96%, and cases increased by 29.9% in those under 50 and 41.8% in those over 50. Discussion: Data from DataSus do not align with international studies regarding the early-onset colorectal cancer rise but highlight racial and regional epidemiological differences in Brazil and Espírito Santo. Conclusion: Colorectal cancer is an increasing national burden, controllable through prevention, early diagnosis, and treatment. This study’s epidemiological data indicate regional disparities requiring further investigation.